Case Report: Therapeutic effect of hypofractionated radiotherapy using HyperArc for giant cavernous sinus hemangiomas - Yang, Mengqi; Peng, Zhaoming; Li, Xin; Chen, Baodong; Peng, Feng; Liu, Yajie (Frontiers in Oncology, 2025)
BackgroundCavernous sinus hemangiomas (CSH) are considered benign vascular skull base tumors. Surgical therapy is the primary treatment due to the neurological deficits resulting from the compressive effects of the mass. However, patients with tumors located in critical areas or those with large tumor volume, surgical resection may be difficult or even unfeasible.Case DescriptionWe report the case of a female patient with a 10-year history of progressive right orbital swelling and visual impairment. Imaging revealed a giant CSH with a tumor volume of 144 cm³. The patient underwent limited debulking surgery one year prior, with substantial residual tumor burden and persistent right facial swelling, particularly in the periorbital region.InterventionThe patient subsequently received hyperarc-based hypofractionated radiotherapy, delivered at a dose of 30 Gy in 10 fractions (3 Gy per fraction), followed by clinicoradiologic assessments at 6-month intervals.OutcomeRadiologic evaluation at 6 months post-radiotherapy demonstrated a 69% reduction in tumor volume. Significant improvement in facial swelling and restoration of facial symmetry were observed. However, right-sided ptosis and vision loss persisted, likely due to irreversible optic nerve damage. A transient alopecia noted at 2 months post-treatment resolved completely by the 6-month follow-up. No acute or late radiation-related toxicities were reported during a 13-month follow-up period.ConclusionThe treatment achieved marked tumor regression and clinical improvement with an excellent safety profile. Hypofractionated radiotherapy may be serve as an alternative effective approach in these unresectable lesions with a favorable safety profile.